Access to information on contaminated areas in the State of São Paulo: an analysis from the perspective of Eco-92 Principle 10 and transparency legislation - Ferreira, Rodrigo Galdino (My University, 2022)
The Environmental Agency of the State of São Paulo (Cetesb) is the agency responsible for developing actions to control, license, supervise, and monitor potentially polluting activities in São Paulo. As such, it needs to follow specific standards, including those related to ensuring access to environmental information provided for in various legislations, such as federal law no 12527/2011 — known as the Free-dom of Information Act (LAI) — and Principle 10 of the Rio Declaration on Environment and Development (P10). By reviewing the literature and analyzing documents on the theme, our research promoted a case study of the Cetesb portal, assessing, in particular, the information available in its menu for the dissemina-tion of data on contaminated areas. We concluded, by a quali-quantitative and descriptive research, that it fails to fully meet Principle 10 since, out of the 13 LAI topics directly associated with the theme, five (40%) were fully met; four, (30%) partially; and four (30%), unmet. The most critical points found concern the non-compliance with active transparency criteria and the lack of mechanisms to encourage participation and social control.
Keywords: Comunicação Social; UNIDADE::SECRETARIA DE INTEGRIDADE PÚBLICA (SIP); Transparency; Access to information; Social control; Principle 10 (P10) of the Rio Declaration on Environment and Development.; Environmental Agency of the State of São Paulo; ASSUNTO::Comunicação Social